Speleoclimate dynamics in Santana Cave (PETAR, S(a)over-tildeo Paulo State, Brazil): general characterization and implications for tourist management - Lobo, Heros A. S.; Boggiani, Paulo C.; Perinotto, Jose A. J. [UNESP] (Societa Speleologica Italiana, 2015)
Show caves provide tourists with the opportunity to have close contact with natural underground spaces. However, visitation to these places also creates a need for management measures, mainly the definition of tourist carrying capacity. The present work describes the results of climate monitoring and atmospheric profiling performed in Santana Cave (Alto Ribeira State and Tourist Park - PETAR, Brazil) between 2008 and 2011. Based on the results, distinct preliminary zones with different levels of thermal variation were identified, which classify Santana Cave as a warm trap. Two critical points along the tourist route (Cristo and Encontro Halls) were identified where the temperature of the locality increased by 1.3 degrees C when tourists were present. Air flow from the inner cave to the outside occurs during the austral summer, and the opposite flow occurs when the outside environment is colder than the air inside the cave during the austral winter. The temperature was used to establish thresholds to the tourist carrying capacity by computing the recovery time of the atmospheric conditions after the changes caused by the presence of tourists. This method suggests a maximum limit of approximately 350 visits per day to Santana Cave. The conclusion of the study is that Santana Cave has an atmosphere that is highly connected with the outside; daily variations in temperature and, to a lesser extent, in the relative humidity occur throughout the entire studied area of the cave. Therefore, the tourist carrying capacity in Santana Cave can be flexible and can be implemented based on the climate seasonality, the tourism demand and other management strategies.
Keywords: show caves; cave management; tourism impacts; microclimate; tourist carrying capacity